Assessing the Effectiveness of Innovation Grants – Evidence from the Irish Innovation Panel - Stephen Roper; Nola Hewitt-Dundas (European Regional Science Association (ERSA), 2005)
Innovation grants are a ubiquitous feature of industrial support regimes across the industrial world. Evidence on their effectiveness is less widespread, however, due to a lack of consistent longitudinal or panel data on innovation outcomes and company performance. In this paper we investigate the effectiveness of R&D and innovation grants support in Ireland and Northern Ireland using panel data and a sample selection approach to the modelling of grant impacts. The study is based on the Irish Innovation Panel which provides panel data on the innovation activities of manufacturing firms in Ireland and Northern Ireland over the 1991-2002 period. The use of panel data allows us to investigate the medium to long-term effect of innovation grant support. In other words, we are able to identify whether the receipt of an innovation grant merely increases innovation activity in the short-term or has any lasting effect on either innovation capability or firms' technological trajectory. The latter outcome is clearly desirable for any region or nation seeking to use innovation grants as a means of boosting long term competitiveness. The use of a sample selection approach allows us to identify separately the 'selection' and 'assistance' elements of the impact of any innovation grant. In other words, it allows us to control for the positive effects of any targeting of assistance on more innovative or better performing companies and isolate the 'true' effect of any innovation grant. To our knowledge this is the first time this approach has been used to assess the impact of innovation grant support although the technique has been used by the authors in a previous analysis of small business assistance. Our results suggest very different time profiles in terms of the benefits from product and process innovation grants suggesting alternative managerial and regional development strategies. Grant support is also found to have strong positive effects on innovation activity even allowing for a wide range of conditioning effects. Our results therefore suggest the continued value of innovation grant support as an element of regions' industrial support regimes.
Keywords: 330